1985
DOI: 10.1111/j.1600-0447.1985.tb05063.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppression test, TRH test and Newcastle II depression rating in the diagnosis of depressive disorders

Abstract: The dexamethasone suppression test (DST), the thyrotropin releasing hormone (TRH) test and the Newcastle II depression rating (NII) were compared with the clinical diagnosis and evaluated in 61 patients fulfilling the criteria of an affective disorder according to the DSM-III classification. A statistically significant correlation between clinical diagnosis and DST as well as NII, but not between clinical diagnosis and TRH test, was found. There was no correlation between DST and the severity of depression acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1988
1988
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Using the 4 p.m. cut-off value (of 4nmol/l) described above, the identification of salivary cortisol hypersecretion in our sample of juvenile depressives has similar sensitivity (48%) and specificity (91 %) to those studies that found cortisol hypersecretion in depression using serum measurement of cortisol levels (see above). The questionnaire results support the validity ofthe diagnostic method used; their lack of correlation with the cortisol results agrees with other adult findings (Larsen, Bjorum, Kierkegaard, Aggernaes, Krog-Meyer, Lund-Laursen & Mikkelsen, 1985;Brown, Johnston & Mayfield, 1979) and supports their being regarded as independent, concurrent estimators of depression. Salivary cortisol measurement therefore appears to be promising as an alternative way of investigating cortisol hypersecretion in a juvenile inpatient population, and allowing one to minimise the trauma of the investigation.…”
Section: Salivary Cortisol and Depressionsupporting
confidence: 84%
“…Using the 4 p.m. cut-off value (of 4nmol/l) described above, the identification of salivary cortisol hypersecretion in our sample of juvenile depressives has similar sensitivity (48%) and specificity (91 %) to those studies that found cortisol hypersecretion in depression using serum measurement of cortisol levels (see above). The questionnaire results support the validity ofthe diagnostic method used; their lack of correlation with the cortisol results agrees with other adult findings (Larsen, Bjorum, Kierkegaard, Aggernaes, Krog-Meyer, Lund-Laursen & Mikkelsen, 1985;Brown, Johnston & Mayfield, 1979) and supports their being regarded as independent, concurrent estimators of depression. Salivary cortisol measurement therefore appears to be promising as an alternative way of investigating cortisol hypersecretion in a juvenile inpatient population, and allowing one to minimise the trauma of the investigation.…”
Section: Salivary Cortisol and Depressionsupporting
confidence: 84%